Rice bran derivatives alleviate microglia activation: possible involvement of MAPK pathway. Issue 1 (December 2016) - Bhatia, Harsharan; Baron, Julian; Hagl, Stephanie; Eckert, Gunter; Fiebich, Bernd
Abstract Background Hyperactivation of microglia is considered to be a key hallmark of brain inflammation and plays a critical role in regulating neuroinflammatory events. Neuroinflammatory responses in microglia represent one of the major risk factors for various neurodegenerative diseases. One of the strategies to protect the brain and slow down the progression of these neurodegenerative diseases is by consuming diet enriched in anti-oxidants and polyphenols. Therefore, the present study aimed to evaluate the anti-inflammatory effects of rice bran extract (RBE), one of the rich sources of vitamin E forms (tocopherols and tocotrienols) and gamma-oryzanols, in primary rat microglia. Methods The vitamin E profile of the RBE was quantified by high-performance liquid chromatography (HPLC). Microglia were stimulated with lipopolysaccharide (LPS) in the presence or absence of RBE. Release of prostaglandins (prostaglandin (PG) E2, 8-iso-prostaglandin F2α (8-iso-PGF2α )) were determined with enzyme immunoassay (EIA). Protein levels and genes related to PGE2 synthesis (Cyclooxygenase-2 (COX-2), microsomal prostaglandin E synthase-1 (mPGES-1)) and various pro- and anti-inflammatory cytokines (TNF-α, IL-1β, IL-6, and IL-10), were assessed by western blot, ELISA, and quantitative real-time PCR. Furthermore, to elucidate the molecular targets of RBE, the phosphorylated state of various mitogen-activated protein kinase (MAPK) signaling molecules (p38 MAPK, ERK 1/2, and JNK) and activation of NF-kB pathway was studied. Results RBE significantly inhibited the release of PGE2 and free radical formation (8-iso-PGF2α ) in LPS-activated primary microglia. Inhibition of PGE2 by RBE was dependent on reduced COX-2 and mPGES-1 immunoreactivity in microglia. Interestingly, treatment of activated microglia with RBE further enhanced the gene expression of the microglial M2 marker IL-10 and reduced the expression of pro-inflammatory M1 markers (TNF-α, IL-1β). Further mechanistic studies showed that RBE inhibits microglial activation by interfering with important steps of MAPK signaling pathway. Additionally, microglia activation with LPS leads to IkB-α degradation which was not affected by the pre-treatment of RBE. Conclusions Taken together, our data demonstrate that RBE is able to affect microglial activation by interfering in important inflammatory pathway. These in vitro findings further demonstrate the potential value of RBE as a nutraceutical for the prevention of microglial dysfunction related to neuroinflammatory diseases, including Alzheimer's disease.